PENTINGNYA PENDIDIKAN ANTI KORUPSI DALAM MENUMBUHKAN BUDAYA ANTI KORUPSI - Ni Ketut Dessy Fitri Yanti Dewi (Jurnal Ilmu Hukum Sui Generis, 2023)
This research discusses the importance of cultivating an anti culture. At present corruption in Indonesia is like a hereditary culture, every generation of corruption must have existed in Indonesia since the royal era until now. This cannot be left alone, because if left unchecked it can destroy this country. In eradicating corruption, of course all levels of society must take part, efforts to eradicate corruption are a shared responsibility, not just the government. Therefore, eradicating corruption must involve all relevant stakeholders, namely the government, the private sector and the community. In order to provide sufficient knowledge about what corruption is and its eradication and instill anti-corruption values, it is important for students to receive Anti-Corruption Education. The reasoning for various negative perceptions of the direction of national education which so far is considered not to characterize the nation's personality, especially regarding educational outcomes which tend not to reflect anti-corruption values ​​and principles, so that there must be an increase in intensity through formal education. To put it simply, Indonesia's formal education system has the potential to contribute to addressing the need to combat corruption. Indirect preventive action can be accomplished in one of two ways: focusing on students, and secondly: using understudy strengthening to diminish the debasement climate. The results of this study indicate that Anti-Corruption Education is very important in fostering an anti-corruption culture.